Everyday Life as a Sociocultural Environment of Formation of the Spiritua - Gharagulyan, Arman (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
Everyday life as a sphere of social life is initially perceived as an absolute reality, in which dominates the natural attitude and utilitarian orientation of human thought. Despite this, the basics of spiritual values of society are formed in the context of everyday utilitarian relationships. In traditional culture unity of primary-biological and idealized-moral values were accepted as evident. Since the 18th and 19th centuries, the scope of internal transformations of everyday life has led to the condition where everyday life starts to lose the function of the formation of moral and spiritual values, thus the spiritual sphere is replaced by specific signs and consumereconomic interest.